Therapeutic Effect of Extracellular Vesicles Derived from HIF Prolyl Hydroxylase Domain Enzyme Inhibitor-Treated Cells on Renal Ischemia/Reperfusion Injury - Zhao-Ying Ding; Tao-Tao Tang; Zuo-Lin Li; Jing-Yuan Cao; Lin-Li Lv; Yi Wen; Bin Wang; Bi-Cheng Liu (Karger Publishers, 2022)
Introduction: Acute kidney injury (AKI) is a major public health problem worldwide. However, there is no definitive therapies to treat established AKI. In this study, we used FG-4592 to induce hypoxia inducible factor (HIF) expression in cells and then explored whether the extracellular vesicles (EVs) secreted by HIF-upregulated cells could alleviate ischemia/reperfusion injury (IRI)-induced AKI. Methods: FG-4592/HK2-EVs and FG-4592/HEK293-EVs were prepared by treating HK2 or HEK293 cells with FG-4592 for 24 h, respectively. HK2 cells under hypoxia were treated with FG-4592/HK2-EVs or FG-4592/HEK293-EVs to observe the therapeutic effect of EVs on H/R-induced apoptosis and inflammation. Mice were treated with FG-4592/HEK293-EVs after IRI to observe whether FG-4592/HEK293-EVs treatment could alleviate ischemic AKI. Results: The expression of HIF was induced by FG-4592 in a dose-dependent manner in HK2 and HEK293 cells under normoxia. In vitro, FG-4592/HK2-EVs and FG-4592/HEK293-EVs inhibited apoptosis and inflammation induced by H/R. In vivo, treatment with FG-4592/HEK293-EVs significantly ameliorated renal tubular injury and inflammation caused by IRI. In addition, the expression of HIF-1α in cells and kidneys was significantly downregulated by FG-4592/HK2-EVs and FG-4592/HEK293-EVs treatment. Conclusion: This study demonstrated that EVs derived from HK2 or HEK293 cells after FG-4592 treatment could alleviate renal tubular injury and inflammation, suggesting a novel therapeutic role of FG-4592/EVs in the treatment of AKI.